Pengaruh Iklim Organisasi Terhadap Kepuasan Kerja Dengan Komitmen Organisasi Sebagai Variabel Mediasi - Rustini, Titin; Muslichah, Muslichah (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
The goal of this study is to look at how organizational climate affects job satisfaction, using organizational commitment as a mediator variable. This study uses a survey method to conduct a causal study. Population target in this research is civil servant National Unity and Politics Agency in Pasuruan City. 50 civil servants participated in this study. The analysis methods that used in this research was path analysis. The findings of this study show that: 1) organizational climate has a significant positive impact on organizational commitment, 2) organizational climate has a significant positive impact on work satisfaction, 3) organizational commitment has a significant positive impact on job satisfaction, and 4) organizational commitment mediates the effects of organizational climate on job satisfaction.